2001
DOI: 10.1046/j.1471-4159.2001.00311.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic valproate treatment decreases the in vivo turnover of arachidonic acid in brain phospholipids: a possible common effect of mood stabilizers

Abstract: Both (Li 1 ) and valproic acid (VPA) are effective in treating bipolar disorder, but the pathway by which either works, and whether it is common to both drugs, is not agreed upon. We recently reported, using an in vivo fatty acid model, that Li 1 reduces the turnover rate of the second messenger arachidonic acid (AA) by 80% in brain phospholipids of the awake rat, without changing turnover rates of docosahexaenoic or palmitic acid. Reduced AA turnover was accompanied by down-regulation of gene expression and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
111
3
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(129 citation statements)
references
References 36 publications
12
111
3
3
Order By: Relevance
“…LCn-3PUFA supplementation in conjunction with standard pharmacotherapy may lead to additive improvements in membrane function, as lithium and valproate treatment is associated with decreased AA turnover without altering DHA turnover (Chang et al, 2001). Although symptom improvement in this study was not related to primary mood-stabilizing medication, changes in parent rated externalizing symptoms were diminished when participants without a co-morbid diagnosis of psychosis received antipsychotic medication.…”
Section: Discussionmentioning
confidence: 63%
“…LCn-3PUFA supplementation in conjunction with standard pharmacotherapy may lead to additive improvements in membrane function, as lithium and valproate treatment is associated with decreased AA turnover without altering DHA turnover (Chang et al, 2001). Although symptom improvement in this study was not related to primary mood-stabilizing medication, changes in parent rated externalizing symptoms were diminished when participants without a co-morbid diagnosis of psychosis received antipsychotic medication.…”
Section: Discussionmentioning
confidence: 63%
“…88 Studies and case reports also indicate that valproate also has efficacy in mixed episodes. 89 Chronic (30 days) administration of valproate, to produce therapeutically relevant plasma levels (0.2 mM), 90 was shown to decrease the turnover rate of AA 90 but not of DHA 91 in brain phospholipids of unanesthetized rats. Similar to lithium and carbamazepine, chronic VPA decreased rat brain COX activity and PGE 2 concentrations, 92 without altering 5-lipoxygenase or cytochrome P450 protein levels or leukotriene B 4 or thromboxane B 2 concentrations.…”
Section: Valproate and The Aa Cascadementioning
confidence: 97%
“…However, unlike lithium and carbamazepine, valproate did not change the expression or activity of cPLA 2 , nor did it alter sPLA 2 or iPLA 2 expression, or AP-2 DNA binding activity. 90,92,94 Because of this difference, we examined the effects of valproate on other enzymes regulating AA turnover within brain phospholipids, namely Acsl. By isolating microsomes from brain, we showed that valproate acts as an ordered noncompetitive inhibitor of Acsl in vitro (Figure 3), and that its K i for inhibiting arachidonoyl-CoA formation was lower than that for inhibiting formation of docosahexaenoyl-CoA or palmitoyl-CoA.…”
Section: Valproate and The Aa Cascadementioning
confidence: 99%
“…In the case of lithium the reduction was 80%, and it was also subsequently demonstrated that lithium down-regulated the gene expression and protein levels of an AAspecific phospholipase A2 (cPLA2) [148,149]. VPA also decreased the turnover of AA by 33%, with no effect on cPLA2 protein levels [145]. These findings suggest that effects of mood stabilizers on cell membranes -and specifically AA turnover -might be relevant to the pharmacological action of lithium and VPA [143,147].…”
Section: Arachidonic Acid Turnover Is Decreased By Both Lithium and Vpamentioning
confidence: 94%
“…Arachidonic acid metabolism as a target of mood stabilizers is suggested by studies done by Chang et al in 1996 and showing that chronic lithium and VPA treatment of rats results in selective reductions in the turnover rate in the brain phospholipids of AA [145][146][147] (Table 2). In the case of lithium the reduction was 80%, and it was also subsequently demonstrated that lithium down-regulated the gene expression and protein levels of an AAspecific phospholipase A2 (cPLA2) [148,149].…”
Section: Arachidonic Acid Turnover Is Decreased By Both Lithium and Vpamentioning
confidence: 99%